Hitchhiking the Labyrinth - Tom Gage (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
James Moffett’s best friend recalls Moffett’s enduring influence on his own extraordinary career, as well as Moffett’s substantial contributions to AEPL.